NSP2 Is Important for Highly Pathogenic Porcine Reproductive and Respiratory Syndrome Virus to Trigger High Fever-Related COX-2-PGE2 Pathway in Pigs - Du, Li; Wang, Honglei; Liu, Fang; Wei, Zeyu; Weng, Changjiang; Tang, Jun; Feng, Wen-hai (Frontiers in Immunology, 2021)
In 2006, atypical porcine reproductive and respiratory syndrome (PRRS) caused by a highly pathogenic PRRSV (HP-PRRSV) strain broke out in China. Atypical PRRS is characterized by extremely high fever and high mortality in pigs of all ages. Prostaglandin E2 (PGE2) derived from arachidonic acid through the activation of the rate-limiting enzyme cyclooxygenase type 1/2 (COX-1/2) plays an important role in fever. Here, we showed that HP-PRRSV infection increased PGE2 production in microglia via COX-2 up-regulation depending on the activation of MEK1-ERK1/2-C/EBPβ signaling pathways. Then, we screened HP-PRRSV proteins and demonstrated that HP-PRRSV nonstructural protein 2 (NSP2) activated MEK1-ERK1/2-C/EBPβ signaling pathways by interacting with 14-3-3ζ to promote COX-2 expression, leading to PGE2 production. Furthermore, we identified that the amino acid residues 500-596 and 658-777 in HP-PRRSV NSP2 were essential to up-regulate COX-2 expression and PGE2 production. Finally, we made mutant HP-PRRS viruses with the deletion of residues 500-596 and/or 658-777, and found out that these viruses had impaired ability to up-regulate COX-2 and PGE2 production in vitro and in vivo. Importantly, pigs infected with the mutant viruses had relieved fever, clinical symptoms, and mortality. These data might help us understand the molecular mechanisms underlying the high fever and provide clues for the development of HP-PRRSV attenuated vaccines.